Merging of the Slovenian and Austrian state coordinate systems and digital terrain models - Radovan, Dalibor (Geodetski vestnik, 1997)
Slovenian and Austrian national coordinate systems are described comparatively. The parameters for spatial calculation between them were calculated for the purpose of transformation of the Austrian digital terrain model into the Slovenian state plane coordinate system. The Austrian model was interpolated and merged with the Slovenian digital terrain model into a grid with a cell size of 100x100 m
Keywords: Avstrija; digitalni model reliefa; geodezija; koordinatni sistemi; Slovenija; transformacija